2006
DOI: 10.1189/jlb.0106030
|View full text |Cite
|
Sign up to set email alerts
|

Role of urease in megasome formation and Helicobacter pylori survival in macrophages

Abstract: Previous studies have demonstrated that Helicobacter pylori (Hp) delays its entry into macrophages and persists inside megasomes, which are poorly acidified and accumulate early endosome autoantigen 1. Herein, we explored the role of Hp urease in bacterial survival in murine peritoneal macrophages and J774 cells. Plasmid-free mutagenesis was used to replace ureA and ureB with cat in Hp Strains 11637 and 11916. ureAB null Hp lacked detectable urease activity and did not express UreA or UreB as judged by immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 62 publications
3
100
0
5
Order By: Relevance
“…Но H. pylori имеет мощный механизм защиты от су-пероксид-анионов, в частности, связанный с экспрессией ферментов каталазы и супероксиддисмутазы. Кроме того, установлено, что уреаза изменяет рН в фагосомах, что спо-собствует выживанию H. pylori в макрофагах [33]. По неко-торым данным, эта бактерия не только выживает, но и раз-множается в макрофагах, эпителиальных и дендритных клетках [34].…”
Section: а у т о и м м у н н ы е з а б о л е в а н и я и а с с о ц и unclassified
“…Но H. pylori имеет мощный механизм защиты от су-пероксид-анионов, в частности, связанный с экспрессией ферментов каталазы и супероксиддисмутазы. Кроме того, установлено, что уреаза изменяет рН в фагосомах, что спо-собствует выживанию H. pylori в макрофагах [33]. По неко-торым данным, эта бактерия не только выживает, но и раз-множается в макрофагах, эпителиальных и дендритных клетках [34].…”
Section: а у т о и м м у н н ы е з а б о л е в а н и я и а с с о ц и unclassified
“…Despite this engulfment, H. pylori appears to be able to avoid intracellular killing. For example, after phagocytizing H. pylori, neutrophils become activated, but the ingested bacteria are not always eliminated (10,123,124), and H. pylori has been shown to survive for up to 48 h within monocytes and macrophages (14,29,110,126,130,153). There is increasing evidence that H. pylori facilitates this survival by altering phagosome maturation to attenuate the destructive effects of the phagosome.…”
Section: Inability Of the Immune Response To Eliminate H Pylorimentioning
confidence: 99%
“…The appearance of megasomes was reported to be characteristic of type 1 H. pylori strains (14,153), whereas LCVs were observed in macrophages, regardless of the H. pylori strain's vacA or cag status (30,126). The study of isogenic mutant strains of H. pylori has demonstrated that VacA and urease are essential for megasome formation (130,153). Megasomes and LCVs appear to arise 2-4 h after internalization and persist for Ն24 h (14,30,126,130,153).…”
Section: How H Pylori Circumvents Phagocytic Killingmentioning
confidence: 99%
See 2 more Smart Citations